2016
DOI: 10.1186/s12864-016-2892-y
|View full text |Cite
|
Sign up to set email alerts
|

When the brain goes diving: transcriptome analysis reveals a reduced aerobic energy metabolism and increased stress proteins in the seal brain

Abstract: BackgroundDuring long dives, the brain of whales and seals experiences a reduced supply of oxygen (hypoxia). The brain neurons of the hooded seal (Cystophora cristata) are more tolerant towards low-oxygen conditions than those of mice, and also better survive other hypoxia-related stress conditions like a reduction in glucose supply and high concentrations of lactate. Little is known about the molecular mechanisms that support the hypoxia tolerance of the diving brain.ResultsHere we employed RNA-seq to approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 51 publications
1
30
3
Order By: Relevance
“…In marine mammals, transcriptomics has never been used to comprehend the cause of an unknown disease and rarely has it been used to characterize the global gene expression of known marine mammal stressors (Mancia et al, 2014; Niimi et al, 2014; Khudyakov et al, 2015a; Khudyakov et al, 2015b; Fabrizius et al, 2016). Here, we used transcriptomics to compare gene expression patterns to known and unknown disease states of stranded harbor seals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In marine mammals, transcriptomics has never been used to comprehend the cause of an unknown disease and rarely has it been used to characterize the global gene expression of known marine mammal stressors (Mancia et al, 2014; Niimi et al, 2014; Khudyakov et al, 2015a; Khudyakov et al, 2015b; Fabrizius et al, 2016). Here, we used transcriptomics to compare gene expression patterns to known and unknown disease states of stranded harbor seals.…”
Section: Discussionmentioning
confidence: 99%
“…There has been some increase in marine mammal transcriptomic studies, such as a study by Hoffman et al (2013) which suggested that post-mortem samples can be reliable resources for genomic studies. Yet, there have been few studied that use transcriptomics to measure physiological stress responses in marine mammals, and there have been no studies that looked at pathogen responses in these megafauna (Mancia et al, 2014; Niimi et al, 2014; Khudyakov et al, 2015a; Khudyakov et al, 2015b; Fabrizius et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…5399 and 7247) and by the authorities at the University of Tromsø (permit numbers: AAB/06). To minimize the use of animals, the tissues were employed in multiple studies [26, 29, 30, 34]. …”
Section: Methodsmentioning
confidence: 99%
“…The first assembly was generated using only the 300 nt long trimmed paired-end reads (12,473,522 reads) from seal visual cortex [30]. The second assembly was generated using, in addition, all the 150 nt paired-end reads from the hypoxia treated samples (312,047,506 reads).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation